Aqueous two-phase partitioning and characterization of xylanase produced by Streptomyces geysiriensis from low cost lignocellulosic substrates - Poornima, Shanmugam; Divya, Palanisamy; Karmegam, Natchimuthu; Karthik, Vivekanandhan; Subbaiya, Ramasamy (Journal of bioscience and bioengineering, 2020)
Microbial production of xylanase is gaining the commercial importance, due to its wide range of applications from paper and pulp to food and feed industries. Streptomyces geysiriensis was used for the production of extracellular xylanase from lignocellulosic substrates such as rice bran and saw dust, under solid-state fermentation. The influence of pH, temperature and incubation period for the maximum production of xylanase was investigated with 1:2 (w/v) of substrate to moisture ratio at 100 rpm shaking conditions. The maximum production was recorded after 5 days of fermentation with pH 8.0 at 40 °C. The scale-up was done based on the results of optimized parameters using 3 L Applikon autoclavable bioreactor with maximum yield of 186 U/ml after 4 days of fermentation. Extracellular xylanase was separated by partitioning in aqueous two-phase system consisting of 20% polyethylene glycol 6000 and 12% K2HPO4 with maximum yield of 93.97%. The investigation of the effect of pH and temperature and its incubation time showed that xylanase was retained its activity in a pH range of 6.5–8.5, with thermal stability from 20 °C to 60 °C up to 180 min. The presence of metal ions was found to inhibit the activity of xylanase especially Cu2+ and Zn2+. Xylanase was stable both at 4 °C and room temperature (35 °C) for 30 and 9 days respectively. The kinetic parameters Km (0.48 mg/ml) and Vmax (8.33 U/mg) were determined using birchwood xylan as substrate. •Use of rice bran and saw dust as substrates for xylanase production is possible.•Streptomyces geysiriensis yielded up to 93.97% xylanase in solid state fermentation.•Stability of xylanase was ranged from pH 6.5 to 8.5 and 20–60 °C up to 180 min.•Xylanase produced by S. geysiriensis was highly stable for 30 days at 4 °C.